Pola Pendidikan Karakter Santri di Pondok Pesantren Hikmatusysyarief NW Salut - Muhammad Yuslih; Abdul Hafiz (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2022)
This study aims to determine the pattern of character education for students at the Islamic boarding school Hikmatusysyarief NW Salut. This research is included in the type of descriptive qualitative research. The data collection was carried out in three ways: observation techniques, interviews, and documentation. Data analysis follows the Miles-Huberman stage: data reduction, data display, and drawing conclusions or verification. The study results show that the patterns and methods of character education at the Islamic boarding school Hikmatusysyarief NW Salut include them. First, the khalaf pattern, from this khalaf pattern formed the character of students who are creative, fond of reading, honest, peace-loving, communicative, and democratic. The second is the boarding school (dormitory) pattern; from this pattern, the students' character is formed who are religious, honest, tolerant, communicative, care for the environment, care for the social, and love peace. Then the third pattern is the semi-military pattern. This pattern forms the character of students who are responsible, disciplined, independent, and hardworking. The pattern used is completely under the control of the Hikmatusysyarief Islamic boarding school assistants for almost 24 hours. The application of this pattern is intended so that after they graduate, they can live within the norms that have been agreed upon by the community where they live, as well as in the world of work. Keywords: Pattern, Character Education, Islamic Boarding School, Hikmatusysyarief Islamic Boarding School Penelitian ini bertujuan untuk mengetahui pola pendidikan karakter santri di pondok pesantren Hikmatusysyarief NW Salut. Penelitian ini termasuk ke dalam jenis penelitian kualitatif deskriptif. Adapun pengumpulan data dilakukan dengan tiga cara yaitu teknik observasi, wawancara, dan dokumentasi. Sementara analisis data mengikuti tahap Miles-Hubermen yaitu reduksi data, kemudian display data, dan yang terakhir penarikan kesimpulan atau verifikasi. Dari hasil penelitian menunjukkan bahwa pola dan metode pendidikan karakter dipondok pesantren Hikmatusysyarief NW Salut diantaranya. Pertama, adalah pola khalaf, dari pola khalaf ini terbentuk karakter santri yang kreatif, gemar membaca, jujur cinta damai, komunikatif, dan demokratis. Yang kedua pola boarding school (asrama), dari pola ini terbentuk karakter santri yang religius, jujur, toleran, komunikatif, peduli lingkungan, peduli sosial dan cinta damai. Kemudian pola yang ketiga adalah pola semi militer dari pola ini terbentuk karakter santri yang bertanggung jawab, disiplin, mandiri, dan  pekerja keras. Pola yang digunakan ini sepenuhnya dalam kendali para asatiz ponpes Hikmatusysyarief hampir selama 24 jam. Tentu penerapan pola ini, dimaksudkan agar setelah mereka lulus dapat hidup dalam norma-norma yang telah disepakati oleh masyarakat tempat tinggalnya, serta di dunia kerja.